2017
DOI: 10.3389/fncel.2017.00099
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipase A2 of Peroxiredoxin 6 Plays a Critical Role in Cerebral Ischemia/Reperfusion Inflammatory Injury

Abstract: Microglia-mediated inflammation is an important step in the progression of cerebral ischemia/reperfusion injury and the associated production of receptors of immunomoudulation, including Toll-like receptors (TLRs). Peroxiredoxin 6 (Prdx6) has been demonstrated as the endogenous antioxidant protein for its peroxidase properties. However, the role of the independent phospholipase A2 (iPLA2) activity of Prdx6 in stroke has not been well studied. In this study, we evaluated whether blocking the calcium-iPLA2 activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 35 publications
(62 reference statements)
0
25
0
Order By: Relevance
“…Consistent with these results, we found that viability of neurons co-cultured with astrocytes was greater than neurons cultured alone. We used neurobasal medium to support the greater nutritional requirements for the co-cultured neurons [ 28 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with these results, we found that viability of neurons co-cultured with astrocytes was greater than neurons cultured alone. We used neurobasal medium to support the greater nutritional requirements for the co-cultured neurons [ 28 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Transient middle cerebral artery occlusion (MCAO)-reperfusion was performed and cerebral blood flow (CBF) was monitored as described previously [ 26 28 ]. Briefly, adult male Sprague-Dawley rats (250–280 g) were anesthetized with 3.5% chloral hydrate (350 mg/kg), and then placed on a heating pad to maintain body temperature at 37 ± 0.5 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, Prdx6 signaling through TLR4 increases after an ischemic stroke, leading to NfκB-mediated inflammation and cell death [87,100,101]. Similarly, the pharmacological inhibition of aiPLA 2 with MJ33 reduces inflammation in an experimental stroke model, supporting the idea that aiPLA 2 has a pro-inflammatory role in the brain under such conditions [102].…”
Section: Prdx6 Signaling In Diseasementioning
confidence: 96%
“…Also, Prdx6 has been shown to inhibit neurogenesis through downregulation of WDFY 1 -mediated TLR4 signal [30]. Moreover, the pharmacological inhibition of aiPLA2 activity of Prdx6 reduces in ammation in an experimental stroke model [31]. This evidence makes the role of Prdx6 controversial in neurodegenerative diseases, which seems to be linked to the differential expression of Prdx6 and its activity in various neurodegenerative disease models.…”
Section: Discussionmentioning
confidence: 99%